Fluoride Distribution in Groundwaters of Banera Tehsil in Bhilwara District, Rajasthan - Hussain, J.; Sharma, K.C.; Hussain, I. (Asian Journal of Chemistry, 2016)
Fluoride concentration of ground water samples from 79 villages of Banera tehsil of Bhilwara district of Rajasthan was determined. In the tehsil 48 villages (61%) were found to have fluoride concentration more than 1.5 mg/L which is the maximum desirable limit of drinking water standard IS:10500, 1999. 59% inhabitants of these villages have the possibility of fluorosis. 2% Population of the tehsil living in 3 villages intakes more than 5.0 mg/L fluoride with each litre of drinking water. In these villages there is the maximum possibility of dental and skeletal fluorosis. The maximum fluoride concentration in the tehsil is recorded 13.0 mg/L in the groundwater of Kamalpura village.